PANDANGAN HUKUM ISLAM TENTANG STATUS ANAK PEREMPUAN YANG LAHIR KURANG DARI 6 BULAN SETELAH AKAD NIKAH - Hj. Hamsidar (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
The view of Islamic law on the establishment of the law and the guardian of his marriage for a girl born less than 6 months from a pregnant marriage differs between classical fiqh scholars with applicable laws in Indonesia (Law Number 1 of 1974 and KHI). According to the scholars of girls born less than 6 months old, they are illegitimate children and the determination of the marriage and guardian of their marriage cannot be with their biological father. Whereas according to applicable law in Indonesia (Law Number 1 Year 1974 and KHI) a girl born less than 6 months from a pregnant marriage is still a legitimate child and her marriage certificate and guardianship is fixed on her biological father. Because of differences of opinion between the ulama and the applicable law in Indonesia regarding this matter, there are two references which all have a strong foundation or foundation, and depending on which guidelines we want to follow.